Wildlife in the Anthropocene : Conservation after Nature - Lorimer, Jamie, 1979- (Book collections on Project MUSE., 2015)
'Wildlife in the Anthropocene' examines rewilding, the impacts of wildlife films, human relationships with charismatic species, and urban wildlife. Analysing scientific papers, policy documents, and popular media, as well as a decade of fieldwork, Jamie Lorimer explores the new interconnections between science, politics, and neoliberal capitalism that the Anthropocene demands of wildlife conservation.